Self-Instruction Technique in Group Counseling to Reduce Students’ Academic Procrastination Behavior - Saputra, Rikas; Lidyawati, Yenni (Islamic Guidance and Counseling Journal, 2019)
The purpose of this study was to determine the effectiveness of self-instruction technique in group counseling to reduce academic procrastination behavior. Purposive sampling technique was administered followed then by random assignment to determine the participants. The scale which is used 44 items from the Procrastination Assessment Scale for Students (PASS) that had previously been adapted and tested for the validity and reliability with Cronbach alpha 0.91. From the data, the score of academic procrastination behavior was obtained. Then it was categorized into three categories high, moderate, and low academic procrastination. The pre-test posttest control group design was applied to 14 students. Based on the independent t-test result, after being treated with self-instruction technique in group counseling, there were differences in the pretest mean of 84.00 and the posttest mean of 69.28. These results indicate a decrease in academic procrastination approximately 14.71, meaning that academic procrastination through the self-instruction technique decreased by 17.51%. Thus, this research shows that group counseling self-instruction technique effectively reduces academic procrastination behavior.